Acute Coronary Syndromes in Sub‐Saharan Africa: A 10‐Year Systematic Review - Yao, Hermann; Ekou, Arnaud; Niamkey, Thierry; Hounhoui Gan, Sandra; Kouamé, Isabelle; Afassinou, Yaovi; Ehouman, Esther; Touré, Camille; Zeller, Marianne; Cottin, Yves; N’Guetta, Roland (Journal of the American Heart Association, 2022)
Background Data in the literature on acute coronary syndrome in sub-Saharan Africa are scarce. Methods and Results We conducted a systematic review of the MEDLINE (PubMed) database of observational studies of acute coronary syndrome in sub-Saharan Africa from January 1, 2010 to June 30, 2020. Acute coronary syndrome was defined according to current definitions. Abstracts and then the full texts of the selected articles were independently screened by 2 blinded investigators. This systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards. We identified 784 articles with our research strategy, and 27 were taken into account for the final analysis. Ten studies report a prevalence of acute coronary syndrome among patients admitted for cardiovascular disease ranging from 0.21% to 22.3%. Patients were younger, with a minimum age of 52 years in South Africa and Djibouti. There was a significant male predominance. Hypertension was the main risk factor (50%-55% of cases). Time to admission tended to be long, with the longest times in Tanzania (6.6 days) and Burkina Faso (4.3 days). Very few patients were admitted by medicalized transport, particularly in Côte d'Ivoire (only 34% including 8% by emergency medical service). The clinical presentation is dominated by ST-elevation sudden cardiac arrest. Percutaneous coronary intervention is not widely available but was performed in South Africa, Kenya, Côte d'Ivoire, Sudan, and Mauritania. Fibrinolysis was the most accessible means of revascularization, with streptokinase as the molecule of choice. Hospital mortality was highly variable between 1.2% and 24.5% depending on the study populations and the revascularization procedures performed. Mortality at follow-up varied from 7.8% to 43.3%. Some studies identified factors predictive of mortality. Conclusions The significant disparities in our results underscore the need for a multicenter registry for acute coronary syndrome in sub-Saharan Africa in order to develop consensus-based strategies, propose and evaluate tailored interventions, and identify prognostic factors.